A obediência à lei na perspectiva do indivíduo : a percepção imperfeita na teoria da utilidade esperada - Scopel, Rodrigo (2012)
The aim of this work is to propose a new approach to the analysis of the economic theory of crime, individual and its behavior, incorporating the neoclassical concepts on the study and the valuable advances in behavioral economics that will culminate in a basic theoretical model. The main results achieved of the model, considering the given variables and parameters set out, suggest that the violation of a particular set of laws could occur instead of a deliberate intention by an error of the agent's perception. In the second part, the theory revised and the improvement proposed in the first part is applied within the environment of crime that involves the interaction between drinking and driving. A review of the studies conducted over the past 30 years mainly in economics and psychopharmacology support an extended version of the model presented in the first part of the work. The main results lead us to believe that, when the law allows some level of alcohol ingestion before the decision about the abilities, capacity and level of intoxication to drive, can interfere in the decision mechanism of the agent who can commit the crime unintentionally